Bina Mekar Sdn Bhd / Nur Syazilia Md Nazry - Md Nazry, Nur Syazilia (Faculty of Civil Engineering, 2014)
Construction of the road upgrading project Muar — Tangkak , Segamat Johor is good and can be used as a stepping stone especially in industrial training students. There are various methods and problems that may be encountered during construction and for this reason, industry training students are given the opportunity to feel the way to learn something useful for building a future after graduation.